Effects of intradialytic cycling exercise on exercise capacity, quality of life, physical function and cardiovascular measures in adult haemodialysis patients: a systematic review and meta-analysis. Issue 8 (28th March 2018) - Young, Hannah M L; March, Daniel S; Graham-Brown, Matthew P M; Jones, Arwel W; Curtis, Ffion; Grantham, Charlotte S; Churchward, Darren R; Highton, Patrick; Smith, Alice C; Singh, Sally J; Bridle, Chris; Burton, James O
Abstract: Background: Intradialytic cycling (IDC), delivered during haemodialysis (HD), has the potential to improve many health issues. This systematic review and meta-analysis examine the evidence on the effects of IDC on exercise capacity, quality of life (QoL), physical function and cardiovascular health. Methods: Twenty-four databases were searched alongside Internet and hand searching, and consultation with experts. Eligibility criteria were cluster randomized, randomized and quasi-randomized controlled trials (RCTs) of IDC versus usual care in prevalent adult HD patients. Primary outcome measures were exercise capacity (VO2 peak and field tests) and QoL. Secondary measures were cardiac and physical function. Results: Thirteen RCTs were eligible. Eight provided data for use in meta-analyses, which indicated no significant change in VO2 peak (mean difference, MD 1.19 mL/kg/min, 95% confidence interval −1.15 to 3.52, P = 0.3), physical (mean change, MC 1.97, −8.27 to 12.22, P = 0.7) or mental component (MC 3.37, −7.94 to 14.68, P = 0.6) summary scores of the Medical Outcomes Short Form 36, pulse wave velocity (MD −0.57 m/s, −1.55 to 0.41, P = 0.4), systolic (MD −2.28 mmHg, −14.46 to 9.90, P = 0.7) or diastolic blood pressure (MD 2.25 mmHg, −3.01 to 7.50, P = 0.4) following IDC. IDC, however, leads to an improvement in performance on the 6-min walk test (MD 87.84 m, 39.60–136.09, P = 0.0004). All included studies were considered to have high risk of bias. Conclusions: There is insufficient evidence demonstrating whether cycling exercise during HD improves patient outcomes. High-quality, adequately powered RCTs of IDC are required.